Sacrificing Gender: Kierkegaard and the Traumatic Self - Rosfort, René (Interdisciplinary journal for religion and transformation in contemporary society, 2022)
Abstract Kierkegaard’s authorship is saturated with gender biases. And yet, the ossified conceptions of gender that we find in Kierkegaard’s writings are destabilized by his ethical ideal of humanity as a radical equality. This paper will examine the argument that the sacrifice of gender plays a vital function in Kierkegaard’s account of human selfhood. Selfhood is not possible without sacrifice. To exist as a human self is to sacrifice one’s own conceptions of the existential differences that make each and every one of us the unique individual that we are. We are gendered beings, and we cannot escape the traumatic ambiguity of intimacy and alienation endemic to our gendered existence. We have to sacrifice our gendered conceptions of being human in light of a demand for a radical equality beyond gender differences. This sacrifice of gender is an ethical demand that we can never fulfill because of our gendered existence.